Impact of Anaerobic Antibacterial Spectrum on Cystic Fibrosis Airway Microbiome Diversity and Pulmonary Function. Issue 11 (November 2021) - Bozzella, Michael J.; Chaney, Hollis; Sami, Iman; Koumbourlis, Anastassios; Bost, James E.; Zemanick, Edith T.; Freishtat, Robert J.; Crandall, Keith A.; Hahn, Andrea
Abstract : Background: The role of anaerobic organisms in the cystic fibrosis (CF) lung microbiome is unclear. Our objectives were to investigate the effect of broad (BS) versus narrow (NS) spectrum antianaerobic antibiotic activity on lung microbiome diversity and pulmonary function, hypothesizing that BS antibiotics would cause greater change in microbiome diversity without a significant improvement in lung function. Methods: Pulmonary function tests and respiratory samples were collected prospectively in persons with CF before and after treatment for pulmonary exacerbations. Treatment antibiotics were classified as BS or NS. Gene sequencing data from 16S rRNA were used for diversity analysis and bacterial genera classification. We compared the effects of BS versus NS on diversity indices, lung function and anaerobic/aerobic ratios. Statistical significance was determined by multilevel mixed-effects generalized linear models and mixed-effects regression models. Results: Twenty patients, 6–20 years of age, experienced 30 exacerbations. BS therapy had a greater effect on beta diversity than NS therapy when comparing time points before antibiotics to after and at recovery. After antibiotics, the NS therapy group had a greater return toward baseline forced expiratory volume at 1 second and forced expiratory flow 25%–75% values than the BS group. The ratio of anaerobic/aerobic organisms showed a predominance of anaerobes in the NS group with aerobes dominating in the BS group. Conclusions: BS antianaerobic therapy had a greater and possibly longer lasting effect on the lung microbiome of persons with CF, without achieving the recovery of pulmonary function seen with the NS therapy. Specific antibiotic therapies may affect disease progression by changing the airway microbiome. Abstract : Supplemental Digital Content is available in the text.